2003
DOI: 10.1002/jez.a.10250
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial insemination technique to eupyrene and/or apyrene sperm in Bombyx mori

Abstract: The silkworm, Bombyx mori, has a dimorphic sperm system. The eupyrene sperm is the sperm to fertilize eggs and the apyrene sperm plays a crucial role for assisting fertilization. Heat-treated (331C for 96h) Daizo (DH) males, one of the strains in the silkworm, produce only eupyrene sperm, while in triploid males only apyrene sperm are functional. Though both types of males are found to be sterile, double copulation of the two males with a single female greatly increases fertility. Here we examined the fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Parasperm function in the majority of sperm‐heteromorphic species has never been investigated, but there are a few species from the Lepidoptera, the Drosophila obscura species group and the stalk‐eyed flies (Diopsidae), which have been extensively studied. For example, in Lepidoptera, empirical support has been found for both the cheap filler hypothesis (Cook & Wedell, 1999) and the facilitation hypothesis (Sahara & Takemura, 2003). Research on the obscura group of Drosophilids, in particular D. pseudoobscura , has empirically rejected the nutrition (Snook & Markow, 1996) and blocking hypotheses (Snook, 1998) and cast doubt on the cheap filler hypothesis (Snook, 1998).…”
Section: List Of Hypotheses For the Evolution Of Infertile Paraspermmentioning
confidence: 99%
“…Parasperm function in the majority of sperm‐heteromorphic species has never been investigated, but there are a few species from the Lepidoptera, the Drosophila obscura species group and the stalk‐eyed flies (Diopsidae), which have been extensively studied. For example, in Lepidoptera, empirical support has been found for both the cheap filler hypothesis (Cook & Wedell, 1999) and the facilitation hypothesis (Sahara & Takemura, 2003). Research on the obscura group of Drosophilids, in particular D. pseudoobscura , has empirically rejected the nutrition (Snook & Markow, 1996) and blocking hypotheses (Snook, 1998) and cast doubt on the cheap filler hypothesis (Snook, 1998).…”
Section: List Of Hypotheses For the Evolution Of Infertile Paraspermmentioning
confidence: 99%
“…In certain invertebrate species, such as Bombyx mori, it has been suggested that non-fertile sperm aid the successful transfer of the fertile sperm to the site of sperm storage or fertilization in the female [51]. It has been suggested that some morphological forms of human sperm have evolved to perform different roles in relation to sperm competition (e.g.…”
Section: The Question Arises However: What Is the Function Of These mentioning
confidence: 99%
“…Many of these suggest that apyrene sperm have a supporting role, for example in aiding eupyrene sperm transport or activating the eupyrene sperm (e.g. Osanai et al, 1986Osanai et al, , 1987Sahara and Takemura, 2003). Alternatively, they may represent a nutrient source either for the fertile sperm in the spermatheca, or for the female and the developing zygotes.…”
Section: Spermmentioning
confidence: 99%